A constraint upon the basal water distribution and thermal state of the Greenland Ice Sheet from radar bed echoes - Jordan,T; Williams,C; Schroeder,D; Martos,Y; Cooper,M; Siegert,MJ; Paden,J; Huybrechts,P; Bamber,J (The Cryosphere, 2018)
There is widespread, but often indirect, evidence that a significant fraction of the bed beneath the Greenland Ice Sheet is thawed (at or above the pressure melting point for ice). This includes the beds of major outlet glaciers and their tributaries and a large area around the NorthGRIP borehole in the ice-sheet interior. The ice-sheet-scale distribution of basal water is, however, poorly constrained by existing observations. In principle, airborne radio-echo sounding (RES) enables the detection of basal water from bed-echo reflectivity, but unambiguous mapping is limited by uncertainty in signal attenuation within the ice. Here we introduce a new, RES diagnostic for basal water that is associated with wet–dry transitions in bed material: bed-echo reflectivity variability. This technique acts as a form of edge detector and is a sufficient, but not necessary, criteria for basal water. However, the technique has the advantage of being attenuation insensitive and suited to combined analysis of over a decade of Operation IceBridge survey data.The basal water predictions are compared with existing analyses of the basal thermal state (frozen and thawed beds) and geothermal heat flux. In addition to the outlet glaciers, we demonstrate widespread water storage in the northern and eastern interior. Notably, we observe a quasilinear corridor of basal water extending from NorthGRIP to Petermann Glacier that spatially correlates with elevated heat flux predicted by a recent magnetic model. Finally, with a general aim to stimulate regional- and process-specific investigations, the basal water predictions are compared with bed topography, subglacial flow paths and ice-sheet motion. The basal water distribution, and its relationship with the thermal state, provides a new constraint for numerical models.